Impaired PTPN13 phosphatase activity in spontaneous or HPV-induced squamous cell carcinomas potentiates oncogene signaling via the MAP kinase pathway - Hoover, Andrew C (2009)
Human papillomaviruses (HPV's) are a causative factor in over 90% of cervical and 25% of head and neck squamous cell carcinomas (HNSCC's). The C-terminus of the high risk HPV 16 E6 oncoprotein physically associates with and degrades a non-receptor protein tyrosine phosphatase (PTPN13), and PTPN13 loss synergizes with H-Ras(V12) or ErbB2 for invasive growth in vivo. Oral keratinocytes that have lost PTPN13 and express H-Ras(V12) or ErbB2 show enhanced Ras/RAF/MEK/Erk signaling. In co-transfection studies, wild type PTPN13 inhibited Ras/RAF/MEK/Erk signaling in HEK 293 cells that over-express ErbB2, EGFR, or H-Ras(V12), while an enzymatically inactive PTPN13 did not. Twenty percent of HPV negative HNSCC's had PTPN13 phosphatase mutations that did not inhibit Ras/RAF/MEK/Erk signaling. Inhibition of Ras/RAF/MEK/Erk signaling using the MEK inhibitor U0126 blocked anchorage independent growth in cells lacking PTPN13. These findings show PTPN13 phosphatase activity plays a physiologically significant role in regulating MAP kinase signaling.